Training of physical education teachers of elementary schools in the countryside of Ceará - Soares, Stela Lopes; Aguiar, Viviany Caetano Freire; Lima, George Almeida; Almeida, Maria Iranilda Meneses; Araújo, Caio Cesar da Silva; Ferreira, Heraldo Simões (Revista Hipótese, 2022)
The aim is to reflect on the profile of physical education teachers, considering its historical trajectory from the Brazilian educational context. Initially, traditional teaching methodologies were teacher-centered. Based on the studies of García (1995), Tardiff (2002), Gatti (2016), the teacher needs to understand this historical process in order to have parameters as a basis for teaching and be open to new paths, due to their training being continuous and dynamic. The research is field and exploratory, with the locus in the Municipality of Sobral, specifically in elementary schools. The results showed that part of the teachers had no contact with contents related to health promotion and that they did not have some post-graduation about the theme. Therefore, it is necessary to think of the continuing education process as an essential tool in teacher qualification allied with the school to enable new teaching methodologies.